2022
DOI: 10.36660/abc.20210797
|View full text |Cite
|
Sign up to set email alerts
|

O Nível de Endocan Sérico pode ser Usado como Biomarcador para Prever Aterosclerose Subclínica em Pacientes Pré-Diabéticos?

Abstract: Fundamento: Pacientes pré-diabéticos têm um risco aumentado de doença cardiovascular aterosclerótica, e, portanto, a detecção precoce é importante.Objetivo: Nosso estudo teve o objetivo de revelar a usabilidade dos níveis de endocan sérico como biomarcador no diagnóstico de aterosclerose subclínica em pacientes pré-diabéticos, com base em medições de EIMC. Métodos: Os participantes foram classificados de acordo com a presença (n=42) ou ausência (n=42) de pré-diabetes. Os valores de endocan sérico, glicemia em … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Two studies investigated circulatory endocan levels in pre-diabetic patients [ 34 , 47 ]. Arman et al [ 34 ] compared endocan levels between 42 pre-diabetic and 42 healthy controls and found significantly decreased levels of endocan in patients with pre-diabetes (120 [65–185] ng/l vs. 138 [84–300] ng/l, p-value = 0.042).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies investigated circulatory endocan levels in pre-diabetic patients [ 34 , 47 ]. Arman et al [ 34 ] compared endocan levels between 42 pre-diabetic and 42 healthy controls and found significantly decreased levels of endocan in patients with pre-diabetes (120 [65–185] ng/l vs. 138 [84–300] ng/l, p-value = 0.042).…”
Section: Resultsmentioning
confidence: 99%
“…Another recent study showed that median circulating endocan values were higher in adults with prediabetes (n = 59) than in the control group (n = 117), although that difference did not reach statistical significance [ 7 ]. On the contrary, Arman et al [ 28 ] demonstrated lower levels of circulating endocan in subjects with prediabetes (n = 42) compared to healthy controls (n = 42). Boyuk et al [ 29 ] also recorded lower circulating endocan levels in MetS subjects (n = 44) as compared to MetS-free individuals (n = 26).…”
Section: Endocan and Metabolic Syndromementioning
confidence: 97%
“…As for the parameters of glucose homeostasis, Arman et al [ 28 ] showed an inverse association between endocan and fasting insulin levels, whereas a study by Klisic et al [ 30 ] demonstrated a positive association between endocan and fasting glucose and glycated hemoglobin (HbA1c).…”
Section: Endocan and Metabolic Syndromementioning
confidence: 99%
See 2 more Smart Citations